Изгибания правильных многогранников с увеличением объема - Милка, А.Д.; Горькавый, В.А. (Інститут математики НАН України, 2009)
Linear bendings of right convex polyhedra, which increase the volume, are considered. Previous results on volume increasing linear bendings by A.D. Milka, D.D. Bleecker, V.A. Alexandrov are improved. For instance, the obtained relative volume increase for the right tetrahedron is 1,4400047...